Vocationalism varies (a lot): a 12-country multivariate analysis of participation in formal adult learning - Boeren, Ellen; Holford, John (Sage, 2016)
To encourage adult participation in education and training, contemporary policy makers typically encourage education and training provision to have a strongly vocational (employment-related) character, while also stressing individuals’ responsibility for developing their own learning. Adults’ motivation to learn is not, however, purely vocational—it varies substantially, not only between individuals but between populations. This article uses regression analysis to explain motivation among 12,000 learners in formal education and training in 12 European countries. Although vocational motivation is influenced by individual-level characteristics (such as age, gender, education, occupation), it turns out that the country in which the participation takes place is a far stronger explanatory variable. For example, although men’s vocational motivation to participate is higher than women’s in all countries, Eastern European women have significantly higher levels of vocational motivation than men in Western Europe. This supports other research which suggests that, despite globalization, national institutional structures (social, economic) have continuing policy significance.